Tryb rozkazujący – uwagi o definiowaniu pojęcia i zakresie jego użycia w opisach systemu fleksyjnego współczesnego języka polskiego - Bojałkowska , Krystyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of this paper is to present how the imperative mood is defined in the descriptions of the inflection system of the contemporary Polish language. First of all, imperative mood is considered to be the value of one of the inflection categories of mood, and the forms representing it, e.g. zrób! (‘do!’), myj! (‘wash!’) are considered to be in opposition to the forms of the declarative and the conditional moods. On the other hand, the imperative is a grammatical means that expresses the so-called deontic modality and utterances with imperative forms are treated, before anything else, as acts of directive speech. This way of defining the imperative mood is the reason why the status of such forms as wygraj! (‘win!’), otrzymaj! (‘receive!’), (nie) umieraj! (‘[not] die!’) or bądź (szczęśliwy) (‘be [happy]’) is problematic, because they constitute a non-directive use of the imperative mood. The conclusion is that the way of defining the imperative mood in Polish requires clarification.